The Individual and the Holocaust in Icchockas Meras’s Stalemate - Raškevičiūtė, Jurgita Žana (Colloquia, 2017)
This article discusses one of the most important Lithuanian twentieth century novels about the Holocaust – Icchokas Meras’s Stalemate (Lygiosios trunka akimirką, 1963; English translation, 2005). The main goal of the article is contribute to the work’s reception with a thorough discussion of how Meras depicts the individual’s relationship to the Holocaust. The article argues that the novel’s three narrative levels represent three different ways a person could respond to the Holocaust. The stories about the Lipman family’s children, which are told in the novel’s evennumbered chapters, are discussed as raising the question of the relationship between the morality that applies in comfortable, everyday situations and the situation of a person who is forced to make moral decisions in extreme circumstances. The story of the relationships between Isaac Lipman and his friends Esther and Janek, which is presented in the novel’s odd-numbered chapters, is discussed as a story reflecting of people resisting the world’s ghettoization. The main form of resistance against the model of human relations imposed by the Nazi regime is the preservation of neighbourly relations between people of different nationalities – as a way of countering the rational “good sense” that is dictated by the instinct to survive. Isaac and the ghetto commander Schoger’s chess game is seen as capturing the essence of the novel: the battle between two stances regarding the individual’s innate morality represents what happened to Western civilization in the middle of the twentieth century. Isaac’s final decision shows us that a person’s morality does not depend on circumstances but upon a free act of internal will, and it is this perspective on the Holocaust that appeared meaningful to the author of the article.